(Not) going to school in times of climate change: Natural disasters and student achievement - Sarah Gust (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2024)
Climate change poses significant risks due to rising frequency and severity of natural disasters. These disasters can disrupt education through school closures, infrastructure damage, financial stress, and health issues. This study assesses their impact on student achievement by combining US county-level data on FEMA disaster declarations with the Stanford Education Data Archive. Exploiting variation in disasters across counties and years in a staggered two-way fixed effects design, event study estimates reveal a persistent negative effect of natural disasters on student achievement for up to five years post disaster. Counties with above-average per-pupil expenditure show quicker recovery. The study sheds light on effect heterogeneity by gender, socio-economic background, and disaster characteristics.
Keywords: Q54; I21; I25; O44; 330; Natural Disasters; Student Achievement; Education Economics; Disaster Resilience; Human Capital